Body surface area is positively associated with ankle-brachial index - Palmu, Samuel; Kautiainen, Hannu; Eriksson, Johan G.; Hakovirta, Harri; Korhonen, Päivi E. (Science progress (1916), 2024)
Background Ankle-brachial index (ABI) measurement is a widely used diagnostic test for lower extremity artery disease. Previously, a larger body surface area (BSA) has been associated with lower blood pressure and lower 2-h post-load glucose concentrations in the oral glucose tolerance test. Our aim was to evaluate whether BSA has an impact on ABI and the prevalence of lower ABI values. Methods ABI measurements were performed on 972 subjects aged 45 to 70 years at high cardiovascular disease (CVD) risk. Subjects with previously diagnosed kidney disease, CVD, and diabetes were excluded. Their BSA was calculated by the Mosteller formula. Study subjects were divided into ﬁve BSA levels corresponding to 12.5th, 25th, 25th, 25th, and 12.5th percentiles of the total distribution. Effect modification by BSA in ABI between sexes was derived from a four-knot restricted cubic splines regression model. Results After adjustments for age, sex, pulse pressure, glucose regulation, waist circumference, alcohol intake, smoking status, leisure-time physical activity and medication, BSA level had a positive linear relationship with ABI (p for linearity <0.001). When BSA was less than 2.0 m2, there was no difference between the sexes, but when BSA was higher than 2.0 m2, men had higher ABI. Conclusion BSA shows a positive linear relationship with ABI in CVD risk subjects without manifested CVD. The difference in ABI between men and women is modified by BSA and is appreciable when BSA is larger than 2.0 m2.